Technetium-99m-labeled peptides and their applications in radio imaging: advancements in Latin American research - Vaezeh Fathi Vavsari; Saeed Balalaie (Exploration of Drug Science)
A very new and highly specialized category of radiotracers that is still growing is radiolabeled peptides. Radiolabeled peptides, or radiopeptides, are powerful elements for diagnostic imaging and radionuclide therapy. These laboratory-manufactured peptides have gained attention due to their unique properties. The tiny structure of these peptides compared to proteins and antibodies makes them favorable regarding their availability through simple synthesis from amino acids, easy uptake by receptors on cancer cells, and high specificity and affinity for high-quality and accurate radio imaging. This study highlighted the potential of technetium-99m-labeled peptides in advancing diagnostic capabilities in directed research in Latin America.